Pneumonia due to Aspergillus fumigatus and Pneumocystis jirovecii coinfection in a non-HIVinfected patient: Case report. - Martinez Montalvo, Carlos Mauricio (2021)
Invasive pulmonary aspergillosis is a condition that mainly occurs in immunosuppressed patients, and it has a high mortality rate. Pneumonia caused by Pneumocystis jirovecii is a potentially lethal opportunistic infection affecting immunosuppressed patients with different etiology. Coinfection by Aspergillus and P. jirovecii in immunocompetent patients is unusual. We report a case of a patient with no common causes of immunosuppression who developed pneumonia coinfection caused by Aspergillus fumigatus and Pneumocystis jirovecii.